(untitled) (Journal of Partial Differential Equations, 1999)
The system of balance laws of mass, momentum and energy for one- dimensional nonlinear thermoviscoelastic material with fixed and thermally insulated endpoints is considered, and the problem of whether there exists a globally defined smooth thermoviscoelastic process is sloved, i.e there exists such a process.